Eat, live, thrive diet : a lifestyle plan to rev up your midlife metabolism - Demetre, Danna; Thomson, Robyn (WaterBrook, 2019)
Eat, Live, Thrive Diet shows women how they can not only lose excess body fat permanently but also improve their overall health in critical areas such as brain function, resistance to disease, slowing down external aging, and increasing energy. This highly effective eating plan is presented in a compassionate voice by two experienced health coaches who share personal experiences of battling weight and emotional eating issues. Whereas most diets are short-lived or require substantial upkeep to maintain, Eat, Live, Thrive Diet is a viable eating plan that women can adhere to indefinitely. In addition to minimizing sugar intake, the plan emphasizes the importance of short-term intermittent fasting--a simple lifestyle change that makes it easier and more effective for many mature women to reach their health and weight loss goals. The book also highlights health risks and drawbacks of many popular fad diets that can be harmful on a long-term basis.